A new acaremyid rodent (Hystricognathi: Octodontoidea) from the middle Miocene of Patagonia (South America) and considerations on the early evolution of Octodontoidea - Arnal, Michelle (2013)
Octodontoidea is the most speciose and ecologically diverse superfamily of caviomorph rodents. The systematic relation-ships of modern octodontoids is moderately accepted, however, the relationships of fossils (from the Eocene?–middle Miocene) are not clear. In recent years the hypothesis of a complex early evolution of the superfamily has emerged, with “basal octodontoids” representing different evolutionary lineages. The extinct family Acaremyidae may represent one such lineage, consisting of the genera Acaremys, Sciamys, Galileomys, and variably Platypittamys. In this work we de-scribe a new octodontoid rodent recorded in post-Colloncuran? levels exposed at the locality of El Petiso, Northwest of Chubut Province, Argentina. Based on a systematic analysis of dental characters, we conclude that the new specimens correspond to a new species of Sciamys. Additionally, if the post-Colloncuran age for El Petiso is verified, the new species will extend the temporal range of the family Acaremyidae until, at least, the late middle Miocene, as well as the temporal range for the genus Sciamys from the Santacrucian SALMA. Our phylogenetic analyses corroborate the position of the new species as a member of Sciamys, and confirm that Acaremyidae represents an extinct family from Patagonian South America that lived until the middle Miocene. Massoiamys obliquus qualifies as morphological ancestor that pre-announc-es the octodontiform tooth pattern of octodontids. Thus, the octodontiform tooth pattern appears at least twice within the superfamily Octodontoidea.